1
$\begingroup$

In Introduction to Analysis by Trench, there is a proof by cases for the triangle inequality, stated as follows:

$(a),\ if\ a\geq 0, and\ b\geq 0,\ then\ a+b \geq0\ , So\ |a+b| = a+b= |a|+|b|$ $(b),\ if\ a\leq 0, and\ b\leq 0,\ then\ a+b \leq0\ , So\ |a+b| = -a+(-b)= |a|+|b|$ $(c),\ if\ a\leq 0, and\ b\geq 0,\ then\ a+b = -|a|+|b| , So\ |a+b| = |-|a|+|b||\leq |a|+|b|$ $(d),\ if\ a\geq 0, and\ b\leq 0,\ then\ a+b = |a|-|b| , So\ |a+b| = ||a|-|b||\leq |a|+|b|$

What I wanted to understand is the last two statements (c) and (d). I tried to sketch it as follows so it makes sense if that's true: $||a|-|b||=||b|-|a||\leq ||b|+|a||=|b|+|a|$

Is it the way it is done to show the (c) and (d) are true?

$\endgroup$
0
$\begingroup$

You can also obtain the triangle inequality by using $\forall a\;(a\leq |a|)$ and $\forall a \;(|$-$a|=|a|)$ and $\forall a\;(|a|\in \{a,\;$-$a\},$ as follows:

(i). $a+b\leq |a|+b\leq |a|+|b|.$

(ii). -$(a+b)=($-$a)+($-$b)\leq |$-$a|+($-$b)\leq |$-$a|+|$-$b|=|a|+|b|.$

(iii). Now $|a+b|\in \{a+b,\;$-$(a+b)\}$ while $a+b$ and -$(a+b)$ are each $\leq |a|+|b|.$

$\endgroup$
0
$\begingroup$

Yes, that is ok, although the author is getting directly the desired result using that $a = -|a|$ for $a \leq 0$ and $-|a| \leq |a|$ for all $a$.

$\endgroup$
5
  • $\begingroup$ I don't think he is using such. Because he moves to So, where ||b|−|a|| ≤ |a|+|b| and not |b|−|a| ≤ |a|+|b| so that he can use such properties. $\endgroup$ – Papa Sep 12 '18 at 16:52
  • $\begingroup$ Sorry I don't understand what you mean. In my opinion, he/she is making explicit use of those properties $\endgroup$ – Javi Sep 13 '18 at 1:47
  • $\begingroup$ How can you infer ||b|−|a|| ≤ |a|+|b| from only ||b|−|a|| using such properties? $\endgroup$ – Papa Sep 13 '18 at 5:25
  • $\begingroup$ By the 2nd property $-|a| \leq |a|$ then $|b|+(-|a|)=|b|-|a| \leq |b|+|a|$ so if $|b|-|a|\geq0$ then $||b|-|a|| = |b|-|a| \leq |b|+|a|$. On the other hand, if $|b|-|a|<0$ then $|a|-|b|>0$ and proceeding the same as before $||b|-|a|| = ||a|-|b|| \leq |a|+|b|$ $\endgroup$ – Javi Sep 13 '18 at 13:34
  • $\begingroup$ Thanks Javi, that was clear! $\endgroup$ – Papa Sep 13 '18 at 13:49

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.